(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the main factors negatively affecting the environment in the processes of mining and processing of potash ores. Criteria for environmental protection in the production of potash fertilizers are recommended. These criteria have been developed taking into account the geological, geographical and economic conditions of the territory, anthropogenic sources, etc., affecting the environment in this territory.